Investigation the Place of BIAN Standard in Digital Banking Enterprise Architecture - Farzi, Narjes (Technium Social Sciences Journal, 2022)
Today organizations encounter many issues such as newfound technologies, new business models, and rapid variations. Nowadays, following evolutions in the global context, caused by information and communication technology in the field of trade, industry, and specifically information technology, has impelled organizations, companies, and particularly banks to undergo changes and alter their reaction method to the market. In this way, the role of enterprise architecture and using standards and reference models are crucial to the organizations. Accordingly, the organization that wants to be active in the digital transformation and move towards digital banking should be able to implement an agile enterprise architecture and use reference models such as BIAN. The objective of this article is to investigate the role of Business Architecture Industry Network (BIAN) Standard in moving towards digital banking.